2020
DOI: 10.1007/s42729-020-00326-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maize Straw–Derived Biochar on Calcareous Arable Soil Organic Carbon Mineralization Under the Condition of with or Without Nitrogen-Fertilizer Addition

Abstract: The object of this study was to explore the effect of biochar on Loess Plateau calcareous arable soil organic carbon mineralization under the condition of with or without nitrogen-fertilizer addition. Maize straw-derived biochars were prepared at 400 and 800°C (BC400 and BC800), respectively. After physicochemical property determination, biochars were thoroughly mixed with soil at the mass ratio of 1% and 2% respectively, and a control without biochar addition was also arranged. Each treatment was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Despite the successful documentation of the effects of long-term in situ straw returning on soil aggregates’ formation, aggregate-associated organic C fractions, and crop yield in the present work, the following points still merit further attention in the future studies. As also addressed in some recent works [ 40 , 57 ], the accumulation of different SOC fractions should be investigated in relation to the soil properties, particularly pH, Fe/Al oxides, as well as the available/total contents of major nutrients. Future studies should monitor the temporal/spatial changes of EOC contents of the straw amended soils in detail, and characterize the mechanisms undertaking the EOC variations specially in relation to the emissions of greenhouse gases.…”
Section: Future Research Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the successful documentation of the effects of long-term in situ straw returning on soil aggregates’ formation, aggregate-associated organic C fractions, and crop yield in the present work, the following points still merit further attention in the future studies. As also addressed in some recent works [ 40 , 57 ], the accumulation of different SOC fractions should be investigated in relation to the soil properties, particularly pH, Fe/Al oxides, as well as the available/total contents of major nutrients. Future studies should monitor the temporal/spatial changes of EOC contents of the straw amended soils in detail, and characterize the mechanisms undertaking the EOC variations specially in relation to the emissions of greenhouse gases.…”
Section: Future Research Gapsmentioning
confidence: 99%
“…As also addressed in some recent works [ 40 , 57 ], the accumulation of different SOC fractions should be investigated in relation to the soil properties, particularly pH, Fe/Al oxides, as well as the available/total contents of major nutrients.…”
Section: Future Research Gapsmentioning
confidence: 99%
“…In general, adding exogenous nitrogen fertilizer can increase the soil urease and protease activities and promote mineralization to form ammonium nitrogen, thus increasing the net nitrogen mineralization [3]. Wang et al [4] found that net soil ammonification was significantly higher in red loam soils under nitrogen application than in non-nitrogen treatments, and high nitrogen application inhibited soil nitrification. Tian et al [5] showed that adding 250 mg/kg of exogenous N significantly increased the net N mineralization of purple tillage soils.…”
Section: Introductionmentioning
confidence: 99%